Pengembangan Media Pembelajaran Interaktif Berbasis Website Pada Materi Struktur Atom Dan Sistem Periodik Unsur Kelas X SMA/MA Sederajat - Riska, Riska; Erna, Maria; Linda, Roza (FKIP University of Mataram, 2025)
This study aims to develop and evaluate the feasibility of website-based interactive learning media on the topic of atomic structure and the periodic table of elements for grade X students of senior high school (SMA/MA) or equivalent. The development was carried out using the ADDIE model which includes five stages: analysis, design, development, implementation, and evaluation. Data collection included validation of media and materials by experts, teacher and student response questionnaires, and limited trials. The validation results showed that the learning media met the “valid” criteria in all aspects assessed, including content feasibility (92.5%), language (93.75%), presentation (93.75%), graphics (97.91%), and concept structure (95.31%), with an overall average of 94.64% for material experts. Media experts assessed the visual design and software utilization aspects at 92.5% and 100%, respectively, with an average of 96.25%. In this study, the research sample was 10 grade X students of SMAN 7 Pekanbaru and 10 grade X students of SMAN 9 Pekanbaru as well as 2 chemistry teachers in each school. In the implementation stage, a user response trial will be conducted by the research sample. The user response trial by teachers and students also showed very good results, with an overall average score of 91.80% and 91.76%, which is categorized as